Plate size and food consumption: a pre-registered experimental study in a general population sample - Daina Kosīte; Laura M. König; Katie De-loyde; Ilse Lee; Emily Pechey; Natasha Clarke; Olivia Maynard; Richard W. Morris; Marcus R. Munafò; Theresa M. Marteau; Paul C. Fletcher; Gareth J. Hollands (BMC, 2019)
Abstract Background There is considerable uncertainty regarding the impact of tableware size on food consumption. Most existing studies have used small and unrepresentative samples and have not followed recommended procedures for randomised controlled trials, leading to increased risk of bias. In the first pre-registered study to date, we examined the impact on consumption of using larger versus smaller plates for self-served food. We also assessed impact on the underlying meal micro-structure, such as number of servings and eating rate, which has not previously been studied. Methods The setting was a purpose-built naturalistic eating behaviour laboratory. A general population sample of 134 adult participants (aged 18-61 years) was randomly allocated to one of two groups varying in the size of plate used for self-serving lunch: large or small. The primary outcome was amount of food energy (kcal) consumed during a meal. Additionally, we assessed impact on meal micro-structure, and examined potential modifying effects of executive function, socio-economic position, and sensitivity to perceptual cues. Results There was no clear evidence of a difference in consumption between the two groups: Cohen's d = 0.07 (95% CI [− 0.27, 0.41]), with participants in the large plate group consuming on average 19.2 (95% CI [− 76.5, 115.0]) more calories (3%) compared to the small plate group (large: mean (SD) = 644.1 (265.0) kcal, versus small: 624.9 (292.3) kcal). The difference between the groups was not modified by individual characteristics. There was no evidence of impact on meal micro-structure, with the exception of more food being left on the plate when larger plates were used. Conclusions This study suggests that previous meta-analyses of a low-quality body of evidence may have considerably overestimated the effects of plate size on consumption. However, the possibility of a clinically significant effect - in either direction - cannot be excluded. Well-conducted trials of tableware size in real-world field settings are now needed to determine whether changing the size of tableware has potential to contribute to efforts to reduce consumption at population-level. Trial registration The study protocol (https://osf.io/e3dfh/) and data analysis plan (https://osf.io/sh5u7/) were pre-registered on the Open Science Framework.